2006
DOI: 10.1007/s10530-005-8281-0
|View full text |Cite
|
Sign up to set email alerts
|

The Biology of Invasions: The Genetic Adaptation Paradox

Abstract: One of the most relevant topics in the biology of invasion concerns the genetic changes that occur subsequent to a species invasion, an issue of particular focus among conservation biologists. Colonizing a novel environment presents a genetic challenge to invading species because such species surely have not experienced the selective pressures presented by the environment. Here we ask, by what mechanisms and processes do alien species genetically naı¨ve to their new environment, become successful invaders? We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 31 publications
2
68
0
3
Order By: Relevance
“…This contrasts to Wares et al's (2005) review of heterozygozity comparisons between native and invasive populations which suggests that natural selection is the major determinant of evolutionary trajectories of invasive populations. Other genetic mechanisms such as epigenetic preadaptation or post-invasive adaptive mutation (see Perez et al 2006) may have also played a role in the invasive success of T. solanivora. A better understanding of these mechanisms will require further studies on populations and environments in both native and invaded areas through the analysis of nuclear markers and the comparison of fitness-related traits.…”
Section: Genetic Bottlenecks and Invasion Successmentioning
confidence: 99%
“…This contrasts to Wares et al's (2005) review of heterozygozity comparisons between native and invasive populations which suggests that natural selection is the major determinant of evolutionary trajectories of invasive populations. Other genetic mechanisms such as epigenetic preadaptation or post-invasive adaptive mutation (see Perez et al 2006) may have also played a role in the invasive success of T. solanivora. A better understanding of these mechanisms will require further studies on populations and environments in both native and invaded areas through the analysis of nuclear markers and the comparison of fitness-related traits.…”
Section: Genetic Bottlenecks and Invasion Successmentioning
confidence: 99%
“…Alternatively, the spreading of this introduced fungus could also be explained by the lack of co-evolution events. Introduced species often arrive in their new environment without coevolved natural enemies and/or competitors from their natural habitats (Allendorf and Lundquist 2003;Pérez et al 2006). It has been suggested that the presence of pathogens, competitive species, and, in more general terms, of high levels of biodiversity, may be a crucial key in making native ecosystems more resilient to colonization (Kennedy et al 2002).…”
Section: Mechanisms Of Invasionmentioning
confidence: 99%
“…Irrespective of the specific underlying mechanisms, rapid shifts in distribution are expected for taxa with good dispersal capabilities (Pearson and Dawson 2003), with such changes in distributions likely impacting on current patterns of biodiversity; for example, taxa that exploit new environments may reduce the niche space of native species and/or alter ecosystem function (Sakai et al 2001;Gabbard and Fowler 2007). An essential part of biodiversity conservation, therefore, is to identify the evolutionary patterns and processes that are associated with successful colonisation (Pérez et al 2006).…”
Section: Introductionmentioning
confidence: 99%